SDG3 good health and wellbeing : re-calibrating the SDG Agenda : concise guides to the United Nations Sustainable Development Goals - Savelyeva, Tamara; Lee, Stephanie; Banack, Hartley (Concise guides to the United Nations Sustainable Development Goals., 2019)
Sustainable Development Goal 3 (SDG3) supplements the 2030 UN Agenda by inspiring ideologies and implementation concerning global health and wellbeing. This book offers insider-view analysis and unique access points into SDG3 implications, community-based responses and innovative proposals, including considerations of Earth as a key stakeholder in sustainability conversations. Written by leading experts in the field, the book presents essays and case studies on sustainability frameworks of Canadian First Nations, cultural groundworks of Aboriginal Australians, HIV/AIDS in Ethiopia, IT-health data analytics in Hong Kong, health-promoting schools in Scotland, Laos, Hong Kong, Australia, and WHO projects in Europe and the Pacific.The book serves as a representative and provocative resource for those wishing to further explore the scope of research, developments, bottom-up interventions and far-reaching visions relating to SDG3.